Tissue Expression of Low and High Molecular Weight Cytokeratins in Lung Carcinoma Sections: Its Correlation with Some Clinic-Pathological Features. (17th November 2014) - Rengifo, Charles E.; Blanco, Rancés; Cedeño, Mercedes; Frómeta, Milagros; Rengifo, Enrique
Abstract : The tissue expression of low (LMW) and high (HMW) molecular weight cytokeratins and Ber-EP4 antigen in both small (SCLC) and non-small (NSCLC) cell lung carcinomas, as well as its correlation with a variety of clinic-pathological features, was evaluated. In general, 43/52 (82.7%) of NSCLC sections showed the expression of at least one type of cytokeratin while only 7/16 (43.7%) of SCLC were stained with both LMW cytokeratin and pan-cytokeratins antibodies. Remarkably, 18/52 (34.6%) of NSCLC were positive to both types of cytokeratins. However, none of SCLC showed this pattern of expression. In NSCLC patients, the increasing levels of HMW cytokeratins expression, as shown by 34 β E12 antibody, correlated with the occurrence of disease recurrence (P = 0.0057 ; Fisher's exact test). Consequently, the expression of HMW cytokeratins was found to be associated with a poor 4-year overall survival of NSCLC patients (P = 0.0315 ; Log rank test), not taking into account the histopathological classification of tumors. Similar results were obtained when 8-year overall survival was assessed (P = 0.0103 ; Log rank test). Our results could suggest the assessment of HMW cytokeratins in a larger series of NSCLC samples in order to confirm the potential prognostic value of them.